A bibliometric and systematic review of scientific publications on metaverse research in architecture: web of science (WoS) - Avinc, Guenes Mutlu; Yildiz, Asli (Springer, 2024)
The global trends related to the concept of Metaverse in architecture have significantly expanded in recent years, thanks to the increasing number of scientific publications. Systematically examining the literature on this topic and identifying research trends and potential directions provides comprehensive data maps, thus charting a roadmap for researchers interested in working in this field. In this context, the research aims to identify the trends and tendencies of the concept of the Metaverse in the scientific literature over time at the primary analysis levels, such as countries, institutions, resources, articles, authors, and research topics. The research conducted with this aim involves a dynamic, visual, and systematic examination of the academic literature on academic publishing using data accessed without year limitations from the Web of Science Core Collection-Citation database. In the research conducted without year limitations, a sample comprising 334 articles published/planned to be published between 2005 and 2024 is analyzed. The bibliometrix R-Tool was used to enhance the analysis, and metadata was obtained from the WoS database. This analysis analyzed publications, citations, and information sources, including the most published journals, the most used keywords, the most cited and leading articles, the most cited academics, and the most contributing institutions and countries. In conclusion, this study aims to define the profile of international academic publishing in the field of the Metaverse, present its development, identify research fronts, detect emerging trends, and uncover the working themes and trends in the Metaverse specific to architecture. This study describes the profile of international academic publishing on the metaverse, presents its development, identifies research frontiers, identifies emerging trends, and reveals metaverse study themes and trends in architecture. As a result, education, virtual perception of space, building operation and maintenance, building evacuation, BIM (Building Information Modeling), cultural heritage, physical environment, built environment/planning, smart home, design and creativity, universal design/accessibility, sustainability, smart city/GIS, urban transportation systems, and in-use evaluation are identified as themes that have been studied in relation to the metaverse concept in architecture and design disciplines.
Keywords: Architecture; Bibliometrix; Metaverse; Biblioshiny; Design; Augmented reality